Correction: Non-reversible heat-induced gelation of a biocompatible Fmoc-hexapeptide in water. Issue 29 (21st July 2020) - Wojciechowski, Jonathan P.; Martin, Adam D.; Du, Eric Y.; Garvey, Christopher J.; Nordon, Robert E.; Thordarson, Pall
Abstract : Correction for 'Non-reversible heat-induced gelation of a biocompatible Fmoc-hexapeptide in water' by Jonathan P. Wojciechowski et al., Nanoscale, 2020, 12, 8262–8267, DOI: ; 10.1039/D0NR00289E .